Recent Development of Nuclear Molecular Imaging in Thyroid Cancer. (21st May 2018) - Liu, Huiting; Wang, Xiaoqin; Yang, Ran; Zeng, Wenbing; Peng, Dong; Li, Jason; Wang, Hu
Abstract : Therapies targeting specific tumor pathways are easy to enter the clinic. To monitor molecular changes, cellular processes, and tumor microenvironment, molecular imaging is becoming the key technology for personalized medicine because of its high efficacy and low side effects. Thyroid cancer is the most common endocrine malignancy, and its theranostic radioiodine has been widely used to diagnose or treat differentiated thyroid cancer. This article summarizes recent development of molecular imaging in thyroid cancer, which may accelerate the development of personalized thyroid cancer therapy.